2006
DOI: 10.1007/bf03344161
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and post-prandial glycemia and their correlation with glycated hemoglobin in Type 2 diabetes

Abstract: In conclusion, both fasting and post-prandial glucose contribute to the determination of HbA1c . Home glucose self-monitoring appears to provide a more accurate assessment of metabolic control than a single plasma glucose measurement in experimental conditions. Fasting glucose could provide a greater contribution to HbA1c in patients with lower HbA1c, while post-prandial glucose seems to play a major role in leaner Type 2 diabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…However, the impact of reduced PPG may to some extent be indirectly included in the present analysis, as HbA1c was used as the measure of glycaemic control. Some studies have suggested that PPG makes a significant contribution to HbA1c in patients who are relatively well controlled, although other studies have been more cautious and have suggested that fasting plasma glucose is a better indicator of HbA1c, particularly in patients with a very high HbA1c concentration …”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of reduced PPG may to some extent be indirectly included in the present analysis, as HbA1c was used as the measure of glycaemic control. Some studies have suggested that PPG makes a significant contribution to HbA1c in patients who are relatively well controlled, although other studies have been more cautious and have suggested that fasting plasma glucose is a better indicator of HbA1c, particularly in patients with a very high HbA1c concentration …”
Section: Discussionmentioning
confidence: 99%
“…Concurrent measurements of fasting plasma glucose and HbA 1c levels during stable therapy are strongly correlated, [4,5]. However, when treatment is intensified, fasting plasma glucose values improve immediately, whereas HbA 1c values lag behind, not reaching a stable new value for 4 months or more.…”
Section: Introductionmentioning
confidence: 99%
“…In hyperglycaemia (post-prandially or in non-controlled diabetes) and to a lesser extent in normoglycaemia, both circulatory proteins and proteins of the endothelium are exposed to (excess) glucose, leading to the slow formation of AGE ( 8 11 ) . During that process, glycation adducts are created on the protein molecule, as a function of glucose levels.…”
Section: Importance Of Glycation For Healthmentioning
confidence: 99%